Alternative approaches to vertebrate ecotoxicity tests in the 21st century: A review of developments over the last 2 decades and current status. (November 2016) - Lillicrap, Adam; Belanger, Scott; Burden, Natalie; Pasquier, David Du; Embry, Michelle R.; Halder, Marlies; Lampi, Mark A.; Lee, Lucy; Norberg‐King, Teresa; Rattner, Barnett A.; Schirmer, Kristin; Thomas, Paul
Abstract: The need for alternative approaches to the use of vertebrate animals for hazard assessment of chemicals and pollutants has become of increasing importance. It is now the first consideration when initiating a vertebrate ecotoxicity test, to ensure that unnecessary use of vertebrate organisms is minimized wherever possible. For some regulatory purposes, the use of vertebrate organisms for environmental risk assessments has been banned; in other situations, the number of organisms tested has been dramatically reduced or the severity of the procedure refined. However, there is still a long way to go to achieve a complete replacement of vertebrate organisms to generate environmental hazard data. The development of animal alternatives is based not just on ethical considerations but also on reducing the cost of performing vertebrate ecotoxicity tests and in some cases on providing better information aimed at improving environmental risk assessments. The present Focus article provides an overview of the considerable advances that have been made toward alternative approaches for ecotoxicity assessments over the last few decades. Environ Toxicol Chem 2016;35:2637–2646. © 2016 SETAC